Hybrid Nanofluids as Renewable and Sustainable Colloidal Suspensions for Potential Photovoltaic/Thermal and Solar Energy Applications - Rasheed, Tahir; Hussain, Tariq; Anwar, Muhammad Tuoqeer; Ali, Jazib; Rizwan, Komal; Bilal, Muhammad; Alshammari, Fwzah H.; Alwadai, Norah; Almuslem, Amani Saleh (Frontiers in Chemistry, 2021)
The comparative utilization of solar thermal or photovoltaic systems has significantly increased to fulfill the requirement of electricity and heat since few decades. These hybrid systems produce both thermal and electrical energy simultaneously. In recent times, increasing interest is being redirected by researchers in exploiting variety of nanoparticles mixed with miscellaneous base fluids (hybrid nanofluid) for these hybrid systems. This new class of colloidal suspensions has many fascinating advantages as compared to conventional types of nanofluids because of their modified and superior rheological and thermophysical properties which makes them appealing for solar energy devices. Here, we have attempted to deliver an extensive overview of the synthetic methodologies of hybrid nanofluids and their potential in PV/T and solar thermal energy systems. A detailed comparison between conventional types of nanofluids and hybrid nanofluids has been carried out to present in-depth understanding of the advantages of the hybrid nanofluids. The documented reports reveal that enhanced thermal properties of hybrid nanofluids promise the increased performance of solar thermal PV/T systems. Additionally, the unique properties such as nanoparticles concentration and type of base fluid, etc. greatly influence the behavior of hybrid nanofluidic systems. Finally, the outlook, suggestions, and challenges for future research directions are discussed.